An Overview of Anti-Eukaryotic T6SS Effectors - Monjarás Feria, Julia; Valvano, Miguel A. (Frontiers in Cellular and Infection Microbiology, 2020)
The type VI secretion system (T6SS) is a transmembrane multiprotein nanomachine employed by many Gram-negative bacterial species to translocate, in a contact-dependent manner, effector proteins into adjacent prokaryotic or eukaryotic cells. Typically, the T6SS gene cluster encodes at least 13 conserved core components for the apparatus assembly and other less conserved accessory proteins and effectors. It functions as a contractile tail machine comprising a TssB/C sheath and an expelled puncturing device consisting of an Hcp tube topped by a spike complex of VgrG and PAAR proteins. Contraction of the sheath propels the tube out of the bacterial cell into a target cell and leads to the injection of toxic proteins. Different bacteria use the T6SS for specific roles according to the niche and versatility of the organism. Effectors are present both as cargo (by non-covalent interactions with one of the core components) or specialized domains (fused to structural components). Although several anti-prokaryotic effectors T6SSs have been studied, recent studies have led to a substantial increase in the number of characterized anti-eukaryotic effectors. Against eukaryotic cells, the T6SS is involved in modifying and manipulating diverse cellular processes that allows bacteria to colonize, survive and disseminate, including adhesion modification, stimulating internalization, cytoskeletal rearrangements and evasion of host innate immune responses.